2010
DOI: 10.4028/www.scientific.net/amr.148-149.799
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Irradiated Preparation of Super Absorbent Resin by Graft Copolymerization of Cellulose and Acrylic Acid/Acrylamide

Abstract: Graft copolymerization of acrylic acid(AA) and acrylamide(AM) on cellulose to prepare super absorbent resin (SAR) under microwave irradiation were investigated using N,N-methylene bis-acrylamide as crosslinking agent, and potassium persulfate/sodium thiosulfate as initiator. The results indicated that it only needed 5min under the microwave level of 320W to obtain the resin with the maximum absorption amount of 1388g•g-1 , under the conditions that the ratio of acrylic acid to cellulose of 14:1, 0.25wt% initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It can make the materials heat evenly and quickly. Grafting of butyl acrylate 6 , propenoic acid 7 and acrylic amide 8,9 onto the starch based on microwave irradiation has been researched recently employing redox initiators. Graft of vinyl functional monomers onto natural resources under microwave conditions in a short reaction time without any redox initiator/ catalyst were reported in recent research.…”
Section: Preparation Of Cellulose Graft Copolymer Based On Combinatiomentioning
confidence: 99%
“…It can make the materials heat evenly and quickly. Grafting of butyl acrylate 6 , propenoic acid 7 and acrylic amide 8,9 onto the starch based on microwave irradiation has been researched recently employing redox initiators. Graft of vinyl functional monomers onto natural resources under microwave conditions in a short reaction time without any redox initiator/ catalyst were reported in recent research.…”
Section: Preparation Of Cellulose Graft Copolymer Based On Combinatiomentioning
confidence: 99%
“…The salt and heat resistances of polymers can be improved through the introduction of hydrophobic monomers comprising long hydrocarbon chains and nonpolar groups. These hydrophobic monomers contain polymerizable CC, and its structures are composed of hydrophobic tails and hydrophilic groups . Micellar nanostructures with different morphologies could form through hydrophobic intramolecular associations and intermolecular interactions with the addition of hydrophobic monomers to the polymerization system .…”
Section: Introductionmentioning
confidence: 99%
“…Although underivatized cellulose is not nearly as hydrophilic as CMC, several investigators have prepared hydrogels by extensive grafting of other monomers onto cellulose, generally employing suitable organic solvent systems (Yoshinobu et al 1992;Wu et al 2008;Chang et al 2009b;Kim and Mun 2009;Buyanov et al 2010;Feng and et al 2010a;Anirudhan et al 2011;Shu and Zhao 2011;Wu et al 2012). Generally, water absorbency values in the range of 60 to 1800 have been reported for such hydrogels, though Kim and Mun (2009) reported a high value of 2500 g/g.…”
Section: Cellulose-synthetic Graft Copolymer Hydrogelsmentioning
confidence: 99%
“…Considerable research has been devoted to the development of copolymers in which CMC is reacted with acrylic monomers and various crosslinking agents to form SAPs (Kuwabara and Kubota 1996;Pourjavadi and Mahdavinia 2005;Pourjavadi and Ghasemzadeh 2006;Abd El-Mohdy 2007;Ibrahim et al 2007;Pourjavadi et al 2007aPourjavadi et al -b, 2008Pourjavadi et al , 2009Pourjavadi et al , 2010Suo et al 2007;Ali et al 2008;Chen et al 2008;Yang et al 2009;El-Din et al 2010;Feng et al 2010a;Lin et al 2010;Bao et al 2011;Eldin et al 2011;Huang et al 2011;Liu et al 2011;Shu et al 2011;Varaprasad et al 2011;Wang et al 2011c). Water absorbency values generally in the range of 40 to 1400 g/g have been reported in such studies, with the highest value reported by Pourjavadi et al (2008).…”
Section: Copolymers Of Cmc By Reaction With Monomersmentioning
confidence: 99%
See 1 more Smart Citation